Gold catalysis: hydrolysis of Di(alkoxy)carbenium ion intermediates as a sensor for the electronic properties of gold(I) complexes - Döpp, René; Lothschütz, Christian; Wurm, Thomas; Pernpointner, Markus; Keller, Sascha; Rominger, Frank; Hashmi, A. Stephen K. (Organometallics, 2011)
Six different cationic gold(I) complexes LAu+ were converted to the corresponding di(alkoxy)carbenium ions by reaction with ethyl 2,5-dimethylhexa-2,3-dienoate. These conversions were monitored by in situ IR spectroscopy; at room temperature they proceeded in only a few seconds. The ligands L are based on the most popular ligand types in gold catalysis: phosphanes, phosphites, carbenes, and isonitriles. The di(alkoxy)carbenium ions were stable, not short-lived intermediates, and could be characterized. This allowed the kinetic study of the next step, the hydrolytic cleavage to the Hammond-type vinylgold species. Depending on the ligand on gold, large rate differences were detected. Computational chemistry revealed a correlation of the experimental reaction rates with the LUMO energies of the di(alkoxy)carbenium species and the direct influence of the ligand on gold on these LUMO energies. Thus, the di(alkoxy)carbenium ion could be utilized as an easy to use benchmark system for the electronic characterization of LAu+ catalysts by theory, spectroscopy, and kinetic experiments.
Gesehen am 21.06.2022